Implementation of Hindu Religious Education in Tourism Development Building Local Wisdom and Spirituality - Mas Wiartha, Nyoman Gede; Septiviari, Anak Agung Istri M.; Adnyana, I Made Sucipta (Jurnal Penelitian Agama Hindu, 2025)
This study reviews the implementation of Hindu Religious Education in tourism development in Bali with the functionality of local wisdom and spirituality. The rapid growth of the tourism sector in Bali threatens the preservation of local culture and spirituality. This research aims to identify the role of Hindu Religious Education in integrating spiritual and cultural values in tourism management while maintaining a balance between economic aspects and cultural preservation. Through qualitative methods with case studies, data was obtained from in-depth interviews with various related parties. The results of the study show that Hindu Religious Education plays an important role in maintaining and spreading Balinese cultural and spiritual values in the tourism sector. This integration also helps protect sacred places and religious practices from the negative impacts of tourism. However, the main challenge faced is the commercialization of tourism which can come at the expense of the preservation of cultural identity. Thus, tourism management that combines Hindu religious values and local wisdom offers a sustainable model and respects culture. It is important to find a balance between economic development and the preservation of Hindu cultural identity and spirituality in Bali in the long term.